Świadomość nauczycieli w zakresie aktywności głosowej i higieny = Teachers` awareness of the issue of voice emission and hygiene - Kataryńczuk-Mania, Lidia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The Author presents selected aspects of the teachers` voice emission and hygiene. The paper underlines, that the teachers are the group that is highly exposed to the voice difficulties. The paper describes a partial research referring to teachers voice activity. The results show low awareness in the field of voice condition and lack of prophylactic knowledge.
Keywords: emisja głosu; higiena głosu; aktywność głosowa; voice emission; voice hygiene; voice activity